The value of Gray scale, color doppler and ultrasound guided- FNA in detection metastasis to the axillary lymph node in patient with primary breast cancer. - Jabbar, Jinan A.; Fahad, Qusay A.; Al -Tememy, Enam A. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Ultrasound guided fine needle aspiration (FNA) is a quick nonmorbid method of staging disease in the axilla,Color doppler ultrasound is used to differentiate benign lymph node from node that bears metastasis. Objective: To evaluate the utility of ultrasound guided (FNA) of the axillary L.N depending on the size of the primary tumor and the appearance of the lymph node by ultrasound , and to document the difference in color Doppler flow features between benign and malignant lymph node in women with primary breast cancer. Patients and methods: The total number of the patient in the study is (60). Data were collected about tumor size, lymph node appearance and color-power Doppler sonography compared to the result of ultrasound- guided FNA . Lymph node were classified as: Benign: if the cortex was even and measure < 3mm. Indeterminate : if the cortex was even but measure ≥ 3mm, or with focal cortical thickening but cortical thickness <3mm. Suspicious: if cortex focally thickened ≥ 3mm, or the fatty hilum was absent. Color-power Doppler evaluation was based on the morphologic pattern of vascularity ( central, peripheral and mixed). Results: of these (60) patients , ultrasound guided FNA was done to (42) lymph node .The sensitivity and specificity of ultrasound guided FNA to detect metastasis to axillary lymph node in correlation to the size of tumor was 50% in tumor (≤1cm), and 86% in tumor between (1 - 2cm), and 93% in tumor >2cm.The sensitivity and specificity of ultrasound guided FNA to detect metastasis to axillary lymph node was 67% for indeterminate lymph node, and 95% for suspicious lymph node. The sensitivity and specificity of ultrasound guided FNA to detect metastasis to axillary node in correlation to color Doppler flow was 100% for mixed vascularity and 100% for peripheral vascularity. Conclusion: There is a strong significant correlation relationship between the presence of peripheral blood flow in addition to the morphological changes which include focal cortical thickening >3mm and loss of hilum ,and the size of the primary tumor with presence of malignancy in LN in patient with primary breast cancer.